Self-Concept Among Otaku and Weeaboo in Japanese Pop Culture: A Systematic Literature Review - Hani Fadilah Humaira; Nita Trimulyaningsih (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2026)
This study aims to identify and synthesize the findings of previous research on self-concept, covering definitions and criteria related to Otaku and Weeaboo. The method used in this study is a systematic literature review utilizing the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. The article search process utilized the Scopus and PubMed databases. The screening process yielded 15 articles for further analysis. From the results of this analysis, it was found that “Otaku” is a term derived from a Japanese word meaning “home.” This term refers to individuals who enjoy spending time at home pursuing hobbies related to Japanese pop culture, such as watching anime, playing computer and video games, and reading manga and novels. Additionally, “Weeaboo” is a term for non-Japanese individuals who are so fascinated by Japanese pop culture that it leads to a desire to become Japanese. These two terms often overlap and share similar criteria. The self-concept of Otaku and Weeaboo individuals is shaped by their interest in Japanese pop culture, such as anime, manga, games, and novels. Even within the Weeaboo community, they view themselves as part of the Japanese people. This self-concept is further strengthened by community involvement, whether among Otaku or Weeaboo.Penelitian ini bertujuan untuk mengidentifikasi dan mensintesis temuan-temuan penelitian sebelumnya mengenai konsep diri yang mencakup definisi hingga kriteria pada Otaku dan Weeaboo. Metode yang digunakan dalam penelitian ini berupa tinjauan pustaka sistematis dengan alat bantu Preferred Reporting Items for Systematic Reviews and Analyse (PRISMA). Proses pencarian artikel menggunakan databese Scopus dan PubMed. Hasil penyaringan mendapat 15 artikel untuk dianalisis lebih lanjut. Dari hasil analisis tersebut, ditemukan bahwa Otaku merupakan istilah yang berasal dari kata Jepang yang berarti “rumah”. Istilah ini diperuntukkan bagi individu yang senang menghabiskan waktu di dalam rumah untuk melakukan hobinya yang berkaitan dengan budaya pop Jepang seperti menonton anime, bermain komputer dan video game, serta membaca manga dan novel. Selain itu, Weeaboo merupakan istilah bagi individu non-Jepang yang tertarik dengan budaya pop Jepang hingga menimbulkan keinginan untuk menjadi orang Jepang. Kedua istilah ini seringkali tumpang tindih dan memiliki kriteria yang mirip. Konsep diri pada individu Otaku dan Weeaboo terbentuk melalui ketertarikan mereka pada budaya pop Jepang seperti anime, manga, game, dan novel. Bahkan dalam komunitas Weeaboo, mereka menilai diri sebagai bagian dari orang Jepang. Konsep diri ini semakin kuat karena adanya keterlibatan komunitas, baik pada Otaku maupun Weeaboo.